Efficacy and safety of brexpiprazole as adjunctive treatment in major depressive disorder: overview of four short-term studies. (13th October 2019) - Thase, Michael E; Zhang, Peter; Weiss, Catherine; Meehan, Stine Rasmussen; Hobart, Mary
ABSTRACT: Background : There is a need for effective, safe and well-tolerated pharmacotherapies for patients with major depressive disorder (MDD) who have inadequate response to antidepressant treatments (ADTs). This analysis aimed to summarize the short-term efficacy and safety of adjunctive brexpiprazole in adults with MDD. Research design and methods : A pooled analysis of data from the 6-week, randomized, double-blind treatment phases of four studies of adjunctive brexpiprazole 1–3 mg/day versus placebo in outpatients with MDD and inadequate response to ADTs (n = 1, 853). Efficacy was measured by Montgomery–Åsberg Depression Rating Scale (MADRS) scores, and safety by treatment-emergent adverse events (TEAEs). Results : ADT + brexpiprazole 2–3 mg/day showed greater improvement in MADRS Total score from baseline to Week 6 than ADT + placebo (least squares mean difference: −2.15; confidence limits: −2.82, −1.48; p < 0.0001; Cohen's d effect size: 0.33). TEAEs with incidence ≥5% with ADT + brexpiprazole 1–3 mg/day were akathisia (8.0% versus 2.6% with ADT + placebo), headache (5.8% versus 6.0%), and weight increased (5.8% versus 1.6%). Conclusions : Adjunctive brexpiprazole is an efficacious and well-tolerated treatment option for adult patients with MDD and inadequate response to ADTs. Study limitations included a lack of active comparator.